A COMPARISON OF THE INTERACTIVE METADISCOURSE IN THE ABSTRACTS OF ARTICLES WRITTEN BY INDONESIAN AND NES SCHOLARS - Eva Nur Mazidah (Department of Master of Linguistic, Universitas Airlangga, 2019)
An abstract plays an important role in an article because it becomes the face of the whole paper. Besides, voluntarily or involuntarily when writing an abstract, a writer also applies metadiscourse markers to communicate effectively by organizing, interacting, and showing the stance. Thus, the application of metadiscourse in an abstract becomes an interesting object to examine. This study is aimed at examining interactive and interactional metadiscourse suggested by Hyland (2005) in 50 abstracts written by Indonesian scholars and 50 abstracts written by NES scholars, 100-250 word range, taken from TEFLIN journal and ELT journal. The results show that NES scholars apply more metadiscourse markers than Indonesian scholars (83.14 versus 76.37). NES, in details, apply more code glosses, and transition markers, while Indonesian scholars apply more frame markers and evidentials, and the similar result is found in endophoric markers (8.9 for both groups of scholars). But, from overall cases and variants, metadiscourse markers by Indonesian scholars are more varied than those of NES scholars (618 versus 559 cases, 66 versus 48 variants). Differences are mostly influenced by cultural interferences (Friedlander, 1987; Hyland, 2005; Abdi, 2009; Sanjaya et al., 2015; Mu et al., 2015). Apart from what causes the differences, the result of T-test shows that the difference in metadiscourse markers applied by both scholars is not significant. It means that metadiscourse markers applied by both groups of scholars are similar.